Diagnostic accuracy of transient elastography (FibroScan) versus the aspartate transaminase to platelet ratio index in assessing liver fibrosis in chronic hepatitis B: The role in primary care setting. Issue 10 (13th June 2011) - Lesmana, C Rinaldi A; Salim, Simon; Hasan, Irsan; Sulaiman, Andri S; Gani, Rino A; Pakasi, Levina S; Lesmana, Laurentius A; Krisnuhoni, Ening; Budihusodo, Unggul
Abstract : Background: A non-invasive method to assess liver fibrosis by measuring liver stiffness with transient elastography (TE) has been recently introduced. The role of TE among chronic hepatitis B (CHB) patients in starting antiviral therapy in the primary care setting is still controversial because of its high cost. The AST to platelet ratio index (APRI) could be a much cheaper alternative. Objectives: This study compares the diagnostic accuracy of TE and APRI in assessing liver fibrosis in CHB patients. Patients and Methods: A cross-sectional study in CHB patients intending to start antiviral treatment. Liver fibrosis was staged according to the METAVIR scoring system. Liver stiffness was measured by TE performed on the same day with liver biopsy, while APRI was calculated as follows: APRI=(AST/upper limit of normal)×100/platelet count (10 9 /l). Cutoff levels of liver stiffness and APRI were calculated by using the receiver operating characteristic curve to detect significant liver fibrosis, defined as fibrosis stage F2 or more. Results: 117 patients were enrolled in the study; their mean age was 40.6±10.97 years. The median liver stiffness was 5.9 kPa (2.5–48 kPa) and the median APRI was 0.239 (0.09–2.73). The cutoff level of liver stiffness was 5.85 kPa for ≥F2 with an AUC of 0.614, 60.3% sensitivity, 63.6% specificity, 73.3% PPV, 49.1% NPV and a LR+ of 1.66. The APRI cutoff level was 0.235 for F≥2 with an AUC of 0.693, 64.4% sensitivity, 70.5% specificity, 78.3% PPV, 54.4% NPV and a LR+ of 2.18. Both methods gave comparable diagnostic accuracy. Conclusion: APRI is a useful marker to screen liver fibrosis in the primary care setting when TE is not available.